1990
DOI: 10.1002/pola.1990.080280926
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of emulsifier‐free emulsion polymerization. III. Styrene/nonionic comonomer (2‐hydroxyethyl methacrylate) system

Abstract: SynopsisThe emulsifier-free emulsion polymerizations of styrene in the presence of about 0.33-2.7% (relative to styrene) of the water soluble comonomer, 2-hydroxyethyl methacrylate ( HEMA), and of the initiator, potassium persulfate ( K P S ) , were carried out. It was found that KPS plays a predominant role in the particle nucleation process, since the number density of polymer particles (N,) was dependent on the 0.97-power of [ KPS] . The nucleation ability of HEMA was weak, since N p was dependent only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…4(c,d)]. This incorporation is probably the main reason for postulation of the core-shell particle growth mechanism by Chen et al 10 Similar morphology development was also found in the presence of 8 wt % EA, as shown in Figure 5. However, gray particles existed for a longer time in the polymerization system because of the lower transfer rate of 4VP to the aqueous phase, and apparently a core could be found in the gray particles [ Fig.…”
Section: Morphology Development During the Polymerizationsupporting
confidence: 73%
See 3 more Smart Citations
“…4(c,d)]. This incorporation is probably the main reason for postulation of the core-shell particle growth mechanism by Chen et al 10 Similar morphology development was also found in the presence of 8 wt % EA, as shown in Figure 5. However, gray particles existed for a longer time in the polymerization system because of the lower transfer rate of 4VP to the aqueous phase, and apparently a core could be found in the gray particles [ Fig.…”
Section: Morphology Development During the Polymerizationsupporting
confidence: 73%
“…8,10 However, this explanation is inadequate for the explanation of the phase separation because a core-shell structure should be formed, rather than the anomalous shape, in view of the variation of interfacial tensions, particularly in the copolymerization of a hydrophilic monomer and a hydrophobic one, as discussed in this work. Furthermore, the anomalous morphologies were also found in the soapfree emulsion homopolymerization of St.…”
Section: Morphology Development During the Polymerizationmentioning
confidence: 93%
See 2 more Smart Citations
“…According to the Smith-Ewart theory in which the number density of polymer particles is proportional to the 0.6-power of emulsifier concentration in conventional emulsion polymerization of styrene, they suggest that In N is proportional to the logarithmic value of the comonomer concentration. From data fitting, this number density is proportional to [NaUI], [NaSEM] 2 , [HEMAJ 0 · 17 , and [AAmJ 0 · 19 in the systems of different comonomers, undecylenic isethionate sodium salt (NaUI), 9 sodium salt of 2-sulfoethyl methacrylate (NaSEM), 9 2-hydroxyethyl methacrylate (HEMA), 10 and acrylamide (AAm), 11 respectively. They explained the different power order of the various comonomer by the contribution of the comonomer on the particle nucleation.…”
mentioning
confidence: 99%